2021
DOI: 10.3390/ma15010001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water-Induced Degradation of Polytetrafluoroethylene (PTFE)-Coated Woven Fabrics Mechanical Properties

Abstract: The impact of water-induced degradation on the mechanical properties of the chosen two PTFE-coated, glass threads woven fabrics is investigated in this paper. The paper begins with a survey of literature concerning the investigation and determination of coated woven fabric properties. The authors carried out the uniaxial tensile tests with an application of flat and curved grips to establish the proper values of the ultimate tensile strength and the longitudinal stiffness of groups of specimens treated with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 95 publications
1
8
0
Order By: Relevance
“…For laboratory tests the authors chose two coated woven fabrics having glass threads coated by PTFE. The properties of the PTFE coated woven fabrics are the same as those investigated by Ambroziak and Kłosowski [11]. The S-type and B-type fabrics' main properties, declared by the producers, are very similar, Table 1.…”
Section: Methodssupporting
confidence: 60%
See 3 more Smart Citations
“…For laboratory tests the authors chose two coated woven fabrics having glass threads coated by PTFE. The properties of the PTFE coated woven fabrics are the same as those investigated by Ambroziak and Kłosowski [11]. The S-type and B-type fabrics' main properties, declared by the producers, are very similar, Table 1.…”
Section: Methodssupporting
confidence: 60%
“…The literature concerning the subject of coated woven fabrics is very extensive. Every year new investigations are performed on comprehensive studies on the coated woven fabrics [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Performed investigations have shown that the mechanical parameters of the coated woven fabrics are highly influenced by temperature changes [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the surface roughness of the material is large, the air forms an air cushion in the groove. When the Wenzel model fails, the surface contact state is converted to the Cassie model [7]. In this model, the residual gas in the solid surface groove forms a new solid-liquid-gas composite interface with the droplet and the solid surface, as described in Formula (3):…”
Section: Superhydrophobic Properties Analysismentioning
confidence: 99%